(3GdHSJGf aj EYQGH eTcdGJ GdbQGfs - (3CMeO Hf CHj HcQ Hf YeQ Hf CHj GdNjQ Hf CHj GdgjKe GdMfHdj, CHh GdYHGS GdGMfa,J (B691 (3g` s
(3ChdgG (B:s
(3ShQI GdCfHjGA Ydjge GdSdGe ecjI bhdg YR hLd dGbJQH ddfGS MSGHge (B) (3GdBjI s
(3BNQgG (B:s
(3agPG eG MVQfi ef GhUGa GdYdI hHGddg GdJhajb s
(3GdeNWhW YOO ChQGbgG (B350 (3hQbI UhQJ (B260 (3hQbI HTcd UMjM Ke UhQ GdHGbi YcS GJLGg JUhjQ Gdajdes
(3GdfSNI HgG MhGTs
(3fbdJ Yf fSNI GdeDda dSfI (B690(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs